B Cells Adapt Their Nuclear Morphology to Organize the Immune Synapse and Facilitate Antigen Extraction - Ulloa, Romina; Corrales, Oreste; Cabrera-Reyes, Fernanda; Jara-Wilde, Jorge; Saez, Juan José; Rivas, Christopher; Lagos, Jonathan; Härtel, Steffen; Quiroga, Clara; Yuseff, María-Isabel; Diaz-Muñoz, Jheimmy (Frontiers in Immunology, 2022)
Upon interaction with immobilized antigens, B cells form an immune synapse where actin remodeling and re-positioning of the microtubule-organizing center (MTOC) together with lysosomes can facilitate antigen extraction. B cells have restricted cytoplasmic space, mainly occupied by a large nucleus, yet the role of nuclear morphology in the formation of the immune synapse has not been addressed. Here we show that upon activation, B cells re-orientate and adapt the size of their nuclear groove facing the immune synapse, where the MTOC sits and lysosomes accumulate. Silencing the nuclear envelope proteins Nesprin-1 and Sun-1 impairs nuclear reorientation towards the synapse and leads to defects in actin organization. Consequently, B cells are unable to internalize the BCR after antigen activation. Nesprin-1 and Sun-1-silenced B cells also fail to accumulate the tethering factor Exo70 at the center of the synaptic membrane and display defective lysosome positioning, impairing efficient antigen extraction at the immune synapse. Thus, changes in nuclear morphology and positioning emerge as critical regulatory steps to coordinate B cell activation.